DETERMINACIÓN EXPERIMENTAL DE LA TASA DE DOSIS DE NEUTRONES EN LOS AMBIENTES DEL REACTOR DE INVESTIGACIÓN RP–0 UTILIZANDO DETECTORES POLÍMEROS CR–39 - Aparicio O., C. (2006)
Abstract The neutron dose rate has been measured at different locations inside and outside of RP-0 reactor hall from Peruvian Institute of Nuclear Energy (IPEN); for which it was use a meted based on nuclear tracks detection leaves for charged particles produced by nuclear reaction between neutron and detector material. The used material went CR-39 polymer, to be insensitive to gamma radiation; The detection principle of neutrons is the reaction (n,p) with the nitrogen contained in air, the tracks become visible after chemical etching of polymer. The calibration of CR-39, it was carried out at the thermal column to have is a 95,5% of thermal flux, that is the what want to detect. As a result of polymer calibration, at thermal column, it was obtained the calibration factor that let obtain the value of neutron dose ((1,87 ± 0,19)x10-2 cm2 mSv), and known the irradiation time it was determined the value of neutron dose rate. The most representative values of neutron dose rate to 7 w operating power be: 7,67 mSv/h (± 16%) at the contour of reactor tank, 8,29 mSv/h (± 12%) at the maneuvers bridge over reactor tank, 1,26 mSv/h (± 12%) at operation console and 0,49 mSv/h (± 16%) at physics laboratory. These values are something high and increases the total dose that should be received per year (20 mSv), that is why is not recommended to work at this operating power.